The Effect Of Aloe Vera Gel On Acceleration Of Healing Of Second-Degree Burn Wounds - Zaenal Zaenal; Edi Pramono; Rini Mustamin; Rezqiqah Aulia Rahmat; M. Khalid Fredy Saputra (International Journal of Health Sciences, 2026)
ABSTRACT Second-degree burns are a type of wound that involves the epidermis and part of the dermis and therefore require appropriate treatment to prevent infection and accelerate healing . This study aims to analyze the effectiveness of Aloe vera gel in accelerating the healing process of second degree burns . The study used a quasi-experimental method with two treatment groups . Data were collected through observation of wound conditions and analyzed using statistical tests . The results showed that the use of Aloe vera had a significant effect on accelerating wound healing compared to conventional Active treatments​ ingredients such as aloin , saponin, and lignin in Aloe vera play a role in accelerating tissue regeneration . Therefore , Aloe vera can be used as an alternative natural therapy in the treatment of burns . Keywords : Aloe Vera, Wound Healing , Burns , Natural Therapy